Transcendentalism in the Contemporary Theatrical Text - mashi , Rafid mahmood (International Journal of Psychosocial Rehabilitation, 2019)
Theatrical works are considered, since their inception, to address the problems of society, and simulate its requirements, in addition to the fact that theater is one of the means of entertainment and learning at the same time. Studies dealing with theater have focused on the intellectual aspects that are being addressed, especially the topic of (Transcendentalism), which was dealt with theatrically before and after the popularity of the relatively modern philosophies of the time of philosophy (controversy, suspicion, existence) after the Enlightenment, the trend towards material evidence, and a departure from the world of metaphysics. To determine the work of (transcendental) in the theatrical text, the research intended to study the concept in terms of its emergence, wading and influences, and the concepts that centered on the supremacy of man’s thought over the material, and his belief in intuition whose guide and guide are in the rule of his will be free and rooted from the values of logic within the context of belief ( Transcendentalism in the inherent goodness of human beings, and it is society that spoils its purity. The philosophy of (transcendental) is the interpretation of ideas that cannot be perceived by sense, provided that the prior condition is provided through which knowledge is possible, by studying the initial images so that the perception is correct, and the precedence of understanding over abstract logic is by rejecting ready-made and consumed forms, the reverence of (transcendental) The philosophical for intellectual independence. All this was evident through the projections (transcendental) in the theatrical texts, which were mentioned in the research and taking the model of the play (Death of a Salesman) by the writer (Arthur Miller) as a model for the statement (Transcendental) in more detail.